Pemberdayaan Deteksi Dini Tuberkulosis pada Pegawai UMKM Rere’s Kitchen di Kabupaten Ngawi - Jordan Syah Gustav; Sharfina Sekar Nurriwanti, Nabylla; Kartika Sari, Rizqy; Prima Kartika, Ayu (Jurnal Pengabdian Masyarakat, 2025)
Tuberculosis is an infectious disease that remains prevalent in Indonesia. One informal industry that often escapes attention is the home-based catering industry. This occurs because home-based catering businesses tend to overlook aspects such as ventilation, lighting, and the use of personal protective equipment. Rere’s Kitchen is a home-based catering business located in Ngawi. Initial observations showed that the working area of Rere’s Kitchen lacks proper air circulation, posing a potential risk for tuberculosis transmission if, at any point, an employee becomes infected. Nevertheless, the employees of Rere’s Kitchen already have good knowledge about tuberculosis.This community service activity aimed to improve tuberculosis awareness among the employees of Rere’s Kitchen. The activity was conducted on July 5, 2025, and was attended by 13 employees. The results of the pre-test and post-test showed an 18.88% increase in knowledge following the early detection tuberculosis awareness session.Going forward, it is hoped that local health care facilities can provide regular education on tuberculosis. In addition to education, it is also recommended to conduct tuberculosis screening to enable early detection of individuals showing symptoms of the disease.